Effectiveness of Physical Education Program on the Domains of the University Students, Attitudes toward Physical Fitness - Kadum, Fadhel; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2013)
Objectives: To determine the effectiveness of physical education program on the domains of the university students attitudes of physical activity and health, physical activity and mental health, physical activity and nutrition toward physical fitness. Methodology: A quasi-experimental design is carried out throughout the present study with the application of test-retest approach through the period from February 3rd 2013 to June 30th 2013. The study is conducted on purposive sample of(40) Undergraduate Students at the College of Science University of Baghdad . The sample is Consisted of (20) males and (20) females. Questionnaire of two main parts, Personal and demographic information and students’ attitudes about physical activity is constructed and employed. Result: In general, the results show a significant positive improvement in students’ attitudes toward physical fitness after implementation of the education program. Recommendation: The physical education program should be presented to wide-range number of university students with different fields of interest.